2011
DOI: 10.1002/jmri.22444
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative endplate changes of the lumbosacral spine: Dynamic contrast‐enhanced MRI profiles related to age, sex, and spinal level

Abstract: Purpose: To investigate differences in perfusion profiles between degenerative endplate marrow changes and normal vertebral marrow in relation to spinal level, age, and sex with dynamic contrast-enhanced magnetic resonance imaging (DCE MRI).Materials and Methods: Ninety-two consecutive patients referred for evaluation of low back pain or sciatica, without history of malignant or chronic disease, underwent conventional and DCE MRI of the lumbosacral spine. Fifty-two of them demonstrated degenerative endplate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…35 In older subjects with prominent fatty marrow, the curve shows a relatively flat enhancement slope and very low maximal enhancement followed by a plateau or an almost imperceptible washout. In subjects with a higher proportion of red marrow, the curve displays a steeper enhancement slope, higher maximum enhancement and a washout effect [36][37][38] ( Figure 6). Studies evaluating normal marrow perfusion using semi-quantitative indices derived from TICs produced with the region of interest (ROI) method, have shown that maximum enhancement (E max ) Figure 6.…”
Section: Whole Body Mri and Whole Body Diffusionweighted Imagingmentioning
confidence: 99%
“…35 In older subjects with prominent fatty marrow, the curve shows a relatively flat enhancement slope and very low maximal enhancement followed by a plateau or an almost imperceptible washout. In subjects with a higher proportion of red marrow, the curve displays a steeper enhancement slope, higher maximum enhancement and a washout effect [36][37][38] ( Figure 6). Studies evaluating normal marrow perfusion using semi-quantitative indices derived from TICs produced with the region of interest (ROI) method, have shown that maximum enhancement (E max ) Figure 6.…”
Section: Whole Body Mri and Whole Body Diffusionweighted Imagingmentioning
confidence: 99%
“…At a final step, the 50 discrete point DCE curves obtained from each ROI were fitted by means of a non-linear regression method based on the Marquardt algorithm (19), and to an exponentially modified Gaussian (EMG) equation (16,20,21):…”
Section: Mri Quantitative Image and Data Analysismentioning
confidence: 99%
“…Time to peak (TTPK; expressed in sec) and time to maximum slope (TMSP; expressed in sec) values were obtained from the X-axis of the first derivative function d(DCE)/dt ¼f(t), (Fig. 1), (16,20,21,24). The maximum net contrast enhancement (CE max ; expressed as a.u.)…”
Section: Mri Quantitative Image and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advancements in DCE-MRI have made this technique feasible for a non-invasive in vivo longitudinal quantification of intervertebral disc changes in both normal and experimental animal models. DCE-MRI, which utilizes high-field magnetic systems and high-resolution magnet systems, can detect significant changes in the signal enhancement time course in the region of interest (ROI) of intervertebral discs by using the contrast agent gadopentetate dimeglumine [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%